UNVEILING THE PROGNOSTIC POWER OF EARLY SYMPTOMOLOGY IN MODERATE TO SEVERE FORMS OF COVID-19 DISEASE - Beronja, Branko; Stevanović, Olja; Nikolić, Nataša; Todorović, Nevena; Filipović, Ana; Simić, Jelena; Gazibara, Tatjana; Dotlić, Jelena; Lukić, Biljana; Karan, Aleksandra; Milošević, Ivana (HEALTH CARE, 2024)
Introduction: It is not entirely clear what initial symptoms could predict poorer COVID-19 outcomes. The purpose of this study was to identify the initial COVID-19 symptoms associated with the need for an intensive care unit (ICU) treatment and having fatal outcomes of COVID-19. Methods: A retrospective analysis was conducted on patients who were hospitalized in two health care facilities (in Belgrade and Sombor) from March 2021 to April 2022. Data were collected from the electronic medical records. The main outcomes were treatment in the ICU and ICU mortality. The Cox proportional hazard model was used to identify the initial COVID-19 symptoms associated with the ICU treatment and mortality. Results: This research included 457 patients. The average age of patients was 63.77±13.75 years. The most common initial symptoms of COVID-19 were fever (85.1%), cough (77.2%), and fatigue (54.5%). The least common initial symptoms were hoarseness (2.8%), difficulty swallowing (2.8%), and eye itching (1.7%). The adjusted model showed that being older and having chest pain were independently associated with needing the ICU treatment. Furthermore, being older, having shortness of breath, headache and diarrhea, but absence of nasal congestion, were independently associated with poorer survival. Conclusion: The results of this study emphasize the importance of vigilant monitoring and swift intervention in patients presenting with chest pain, shortness of breath, headache, and diarrhea, particularly among older people.